1991
DOI: 10.1073/pnas.88.20.8900
|View full text |Cite
|
Sign up to set email alerts
|

HOX11, a homeobox-containing T-cell oncogene on human chromosome 10q24.

Abstract: A common chromosomal abnormality in childhood T-cell acute leukemia is a translocation, t(10;14) (q24;qll), that together with the variant t(7;10)(q35;q24) is present in up to 7% of this tumor type. The gene adjacent to the lOq24 region is transcriptionally activated after translocation to either TCRD (14q11) or TCRB (7q35). It encodes a homeobox gene closely related to the developmentally regulated homeotic genes of flies and mammals. The coding capacity of this activated gene, designated HOXII, is undisturbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(138 citation statements)
references
References 40 publications
1
136
1
Order By: Relevance
“…8 A recent analysis of 10 HOX11L2-positive of 81 adult T-ALL patients found HOX11L2 expression to be associated with induction therapy failure, failure to respond to a salvage regimen as well as a higher relapse rate and reduced OS. 20 Due to the large number of subjects in our study we are able to show an independent negative prognostic impact of HOX11L2 expression by multivariate analysis. Also, we are able to confirm the immunophenotype as strong prognostic factor for RFS as well as OS.…”
Section: Hox11l2-positive Thymic T-all With Reduced Outcomementioning
confidence: 61%
“…8 A recent analysis of 10 HOX11L2-positive of 81 adult T-ALL patients found HOX11L2 expression to be associated with induction therapy failure, failure to respond to a salvage regimen as well as a higher relapse rate and reduced OS. 20 Due to the large number of subjects in our study we are able to show an independent negative prognostic impact of HOX11L2 expression by multivariate analysis. Also, we are able to confirm the immunophenotype as strong prognostic factor for RFS as well as OS.…”
Section: Hox11l2-positive Thymic T-all With Reduced Outcomementioning
confidence: 61%
“…Recently, it was found that the homeobox protein HOX11 can bind and likely inhibit PP2A, resulting in the disruption of a G2/M cell-cycle checkpoint in both Xenopus oocytes and a human T-cell line (51). This alteration of the regulation of the cell cycle may be instrumental in the development of human T-cell leukemias that result from translocations that fuse the T-cell receptor ␣-or ␤-chain genes with the HOX11 gene (52,53). An important question is whether HRX fusion proteins together with SET perform a function similar to HOX11 in overcoming a G2/M cell cycle checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were diagnosed and treated at the Princess Margaret Hospital for Children, Perth, Western Australia, and informed consent was obtained from parents, patients, or both as deemed appropriate. Several of the cell lines have been described previously (Kees, 1987;Kees et al, 1987Kees et al, , 1989aKees et al, , b, 1990Kees et al, , 1995Kees et al, , 2003Kennedy et al, 1991;Whitman et al, 2001). CCRF-HSB2 (HSB2) cells were obtained from the American Type Culture Collection; CCRF-CEM (CEM) from the Children's Cancer Institute Australia for Medical Research, Sydney; JURKAT from the Basel Institute for Immunology, Switzerland; ALL-SIL from MRC Laboratory of Molecular Biology, Cambridge, UK; MOLT4 from the German Cancer Research Center, Heidelberg, Germany; DU.528 from the Division of Cancer Biology, Telethon Institute for Child Health Research, Perth.…”
Section: Cell Linesmentioning
confidence: 99%